Colonial media and post independence experience in north Africa - Zaghlimi, Laeed (Media & Jornalismo, 2016)
European colonialism had not only occupied many african countries, exploited their natural resources and deprived their inhabitants of basic rights, but also sought to establish its new political, social, economic and cultural system. However, in order to impose its new rules and values, it had used military forces as well as political and media means to convince and influence people minds and hearts. The press was one of the main arguments of seduction and dissimination of the colonial culture and information. This paper which focuses in its first part on French occupation of North Africa, describes how French colonial authority used and abused the media to perpetuate its presence and set up new forms of values and ideas aimed at destroying local culture and traditions. The second part describes how local populations had reacted to the colonial presence by adopting new forms of opposition and resistance. Again, the ‘indigenous press’ was a determining factor in promoting ideas of militantism, independence and sovereignty. The third part highlights the main phases of the media evolution and experience during the post independence period.